International Similarities of Bank Lending Practices and Varieties of Insolvency Laws: a Comparative Analysis of France and Germany - Ingrid Groessl; Nadine Levratto (Hamburg University, Department Socioeconomics, 2012)
Economic theory conjectures complementarities between the ranking of creditors in formal insolvency proceedings and the use of collateral in bank loan contracts as well as the existence of relational compared to arms length lending. In this paper we seek evidence for these hypotheses taking France and Germany as examples which differ significantly concerning the ranking of in particular secured creditors. On closer scrutiny of empirical studies as well as statistical information we can neither confirm that a high priority for se-cured lenders explains an excessive use of collateral in bank loans nor that a priority for inside collateral promotes relational lending. Regarding relational lending we point to variables lying outside the insolvency law, like culture and history.
Keywords: K12; K22; G21; G33; 330; Insolvency; France; Germany; bank-borrower-relationships; collateral; variety-of-capital-approach; law and finance